Microarray analysis of mdx mice expressing high levels of utrophin: therapeutic implications for dystrophin deficiency. - Baban, D; Davies, K (2008)
Duchenne Muscular Dystrophy (DMD) is a fatal muscle wasting disorder caused by dystrophin deficiency. Previous work suggested that increased expression of the dystrophin-related protein utrophin in the mdx mouse can reduce the dystrophic pathophysiology. Physiological tests showed that the transgenic mouse muscle functioned in a way similar to normal muscle. More recently, it has become possible to analyse disease pathways using microarrays, a sensitive method to evaluate the efficacy of a therapeutic approach. We thus examined the gene expression profile of mdx mouse muscle compared to wild-type mouse muscle and compared the data with that obtained from the transgenic line overexpressing utrophin. The data confirm that the expression of utrophin in the mdx mouse muscle results in a global gene expression profile more similar to that seen for the wild-type mouse. This study confirms that a strategy to up-regulate utrophin is likely to be beneficial in dystrophin deficiency.